ANALISIS PENGARUH HUMAN CAPITAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA UMKM YANG DIMEDIASI INOVASI (Studi UMKM di Wilayah Kecamatan Kare Madiun) - Dwi Susanti; Adya Hermawati; Tatik Mulyati (MANAJEMEN DEWANTARA, 2026)
This study aims to empirically examine and verify the influence of human capital and leadership style on the performance of MSMEs with innovation as a mediating variable, focusing on micro, small, and medium enterprises (MSMEs) in Kare District, Madiun Regency. Theoretically, this research contributes to the development of knowledge in Human Resource Management and Entrepreneurship Management, particularly regarding strategies to enhance innovation and performance among small business actors. Practically, the findings are expected to serve as a reference for MSME practitioners and related institutions, especially the Department of Industry and Trade (Disperindag) of Madiun Regency, in designing policies and strategies that foster innovation-driven MSME growth These findings emphasize that innovation serves as a crucial mechanism linking human capital and leadership style to MSME performance improvement, particularly in adapting to market dynamics and changes in consumer demand within the small business sector.